Utilization of Imperfect Produce of Honey Guava to Improving the Economy and Welfare of Farmers - Mahyuni, Eka Lestari; Aritonang, Evawany Yunita; Soeparno, Wahyu Sugeng Imam (Talenta Publisher Universitas Sumatera Utara, 2023)
Huney guava (Syzygium aqueum) is a potential agricultural product of Secanggang District, Langkat Regency, which is generally sold in fresh fruits. The production of Guava in this area reaches 150 kg per farmer, with 25-30 kg of them remain unsold. This community service aims to disseminate knowledge and technology to farmers about processing honey guava fruit into chips with the trade name